Absence of mutation in miR-34a gene in a Chinese longevity population - Wu, Huan; He, Yong-Han; Xu, Tian-Rui; Kong, Qing-Peng (Dōngwùxué yánjiū, 2015)
DEAR EDITOR Centenarians are a typical longevity model characterized by delayed onset of morbidity in age-related diseases such as cancer, cardiovascular disease, dementia, and stroke （Andersen et al, 2012）. Though there may be a number of underlying mechanisms behind this longevity, curiously it seems that the survival advantage persists in their offspring （Terry et al, 2003）, suggesting a potentially important role for genetic factors. Previous studies suggested that the heritability of human longevity may be ~25% （Herskind et al, 1996; Mcgue et al, 1993）, whicih is consistent with other studies on model organisms that identified several longevity-related genes, such as age-l, daf-2, daf-16, and sir-2 （Friedman ＆ Johnson, 1988; Kenyon et al, 1993; Lin et al, 1997; Tissenbaum ＆ Guarente, 2001）. Likewise, several studies have reported the existence of many mutations related to human longevity （Holstege et al, 2014; Sebastiani et al, 2012）.